Analysis of Ethical Differences in Student Speaking of Educators in SDN Kedungturi and SD Al Islam Plus - Assa’Diah Eka Rahmawati; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2020)
This study aims to describe the differences in speaking ethics of students in SD Al Islam and SDN Kedungturi and describe the causes of differences in the ethics of speaking students against teachers in SD Al Islam and SDN Kedungturi. This study used qualitative research methods. Where this research is researchers used to examine the condition of natural objects. In qualitative research researchers are very important because researchers are key instruments. In this study researchers used triangulation (combined) sources. Research instruments in the form of interviews and observations. Research instruments in the form of interviews and observations. From the results of observations and interviews researchers can answer the problem formulation which is divided into 3 indicators, namely: (1) according to the teacher and from the interview results students are friendly and also polite both at school and outside of school, (2) students speak politely to the teacher, both at inside and outside the classroom, (3) grade 3 students are difficult to talk to using standard language, they are more likely to use language that is easily understood by him. Based on the results of the study it can be concluded there are some differences between the two. But the difference is said to be not too significant. The reason for the existence of these differences is because both have different ways of delivering and applying learning to students. It is also because the environment between the two is very different.